1996
DOI: 10.1074/jbc.271.34.20340
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Topography and Near-neighbor Relationships of the Mitochondrial ATP Synthase Subunits e, f, and g

Abstract: The well characterized subunits of the bovine ATP synthase complex are the ␣, ␤, ␥, ␦, and ⑀ subunits of the catalytic sector, F 1 ; the ATPase inhibitor protein; and subunits a, b, c, and d, OSCP (oligomycin sensitivityconferring protein), F 6 , and A6L, which are present in the membrane sector, F 0 , and the 45-Å-long stalk that connects F 1 to F 0 . It has been shown recently that bovine ATP synthase preparations also contain three small polypeptides, designated e, f, and g, with respective molecular masses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 30 publications
(24 reference statements)
3
63
0
1
Order By: Relevance
“…Furthermore, formation of Su e-Su e homodimers, between two neighboring F o complexes was hypothesized to play an important role in facilitating dimerization of the F 1 F o -ATP synthase complex (4). In support of this model, it was previously shown that bovine Su e could be chemically cross-linked to a protein of a similar size to Su e, thus providing preliminary support for Su e-Su e dimers (10). Direct demonstration of homodimers of Sue, however, has been lacking to date.…”
mentioning
confidence: 65%
“…Furthermore, formation of Su e-Su e homodimers, between two neighboring F o complexes was hypothesized to play an important role in facilitating dimerization of the F 1 F o -ATP synthase complex (4). In support of this model, it was previously shown that bovine Su e could be chemically cross-linked to a protein of a similar size to Su e, thus providing preliminary support for Su e-Su e dimers (10). Direct demonstration of homodimers of Sue, however, has been lacking to date.…”
mentioning
confidence: 65%
“…Oligomycin Activity remaining terminal (Belogrudov et al, 1996) which is predicted to form a transmembrane a-helix by computing methods (not shown). Sodium bromide treatment of the F,F,ATP synthase removed most of the F, subunits (Fig.…”
Section: Strainmentioning
confidence: 99%
“…Additional small polypeptides (subunits e, f and g) have been identified in the bovine enzyme (Walker et al, 1991;Collinson et al, 1994). Investigation of their membrane topography and their proximity with other known subunits of the complex showed the last three polypeptides as being bonafide subunits of the bovine ATP synthase (Belogrudov et al, 1996).…”
mentioning
confidence: 99%
“…Cross-links between two copies of e and cross-links of g with both e and f were also reported [37]. Analysis of animal subunit g revealed the presence of a completely conserved acidic residue (Glu82) in the middle of its single transmembrane helix [38].…”
Section: Discussionmentioning
confidence: 87%
“…Previously, we demonstrated that the N-termini of Fo subunits e and g face the matrix side while their respective C-termini face the cytosolic side of the mitochondrial inner membrane [37]. Cross-links between two copies of e and cross-links of g with both e and f were also reported [37].…”
Section: Discussionmentioning
confidence: 95%